Local Islam as a Site of Meaning Negotiation: Symbolic Re-signification and Religious Experience in the Cokaiba Tradition - Alnugransyah Asri; Abdul Basith Abdullah (Graduate School of UIN Syarif Hidayatullah Jakarta, 2026)
This study examines how ritual symbols, religious experience, and social meanings are negotiated within the Cokaiba tradition as a localized expression of Islam in Halmahera, Eastern Indonesia. Using a qualitative ethnographic case study design, the study draws on semi-structured interviews, participant observation, visual documentation, and document analysis. Fieldwork was conducted in Patani, Central Halmahera. Informants include religious leaders, community elders, youth participants, local scholars, and government officials with direct engagement in the tradition. Data were analyzed thematically to identify patterns of symbolic interpretation, embodied religious practice, and social negotiation. The findings show that ritual elements such as masks, white costumes, mosque miniatures, and collective recitations of ṣalawāt and dhikr are not merely cultural artifacts but are actively reinterpreted as expressions of devotion to the Prophet Muhammad, markers of communal identity, and media of social cohesion. These meanings emerge through lived participation rather than fixed doctrinal interpretation. The study further reveals that Cokaiba functions as a site of lived religion where emotional engagement, intergenerational participation, and embodied ritual practices shape everyday Islamic experience. However, certain symbols particularly masks remain contested, reflecting ongoing negotiation between local ritual heritage and normative Islamic interpretations. The article contributes to scholarship on Islam lokal by demonstrating that religious meaning is continuously produced through processes of symbolic re-signification and discursive negotiation embedded in everyday social life.